ARCHIVES MANAGEMENT AT THE GAJAH SAKTI SUBDISTRICT OFFICE, MANDAU DISTRICT, BENGKALIS REGENCY - Mochammad Wiqal; Virna Museliza (Yayasan Wayan Marwan Pulungan, 2025)
This research discusses archival management at the Gajah Sakti Subdistrict office, Mandau District, Bengkalis Regency. In accordance with the regulations of Law (UU) Number 43 of 2009 concerning Archives, archives are records of activities or events created and received by various institutions, such as state institutions, regional governments, educational institutions and companies. This thesis aims to find out how archives are managed, and what are the inhibiting factors in archives governance at the Gajah Sakti Subdistrict office, Mandau District, Bengkalis Regency. This research method uses a qualitative method with a descriptive approach. The data sources in this research used primary data and secondary data and the data collection methods used were observation, interviews and documentation. The results of this research indicate that archives management is not yet optimal in the Gajah Sakti Subdistrict office, Mandau District, Bengkalis Regency, because the archives storage system is still very simple and inadequate, archives management procedures are not running well, as well as limited Human Resources (HR). ) who understand the knowledge and understanding of archiving. The inhibiting factors are a lack of archival facilities and insufficient supporting funds so that many archives are found piled up in cupboards and not arranged neatly, as well as a lack of skilled personnel in terms of archival management.